Two Threshold Smart Irrigation System for Increasing Crop Yield - Ariani Budi Safarina; Iin Karnisah; Kusnandar Kusnandar (Indonesian Journal of Geography, 2023)
The objective of this research is to create an automated irrigation system using two threshold method for rice farming in the Jorolot irrigation area, Cimahi City, West Java Province, Indonesia, which addresses the problem of fluctuating water supply. This issue includes water deficits during the dry season, which threatens rice growth, and excess water during the rainy season, leading to flooding and crop destruction. The method used includes one-dimensional hydraulic modeling of irrigation channels to determine two threshold of channel water level elevation, as well as water availability quantification based on flood, normal, and dry clusters.  Furthermore, the system's design involved utilizing the Decision Supporting System (DSS) data communication to monitor and respond to dry or flood events in real time, thereby increasing the system's overall performance. The Jorolot irrigation area, which covers 15.5 hectares, sources its water from the Jorolot Dam, with a primary channel length of 1135 m and a secondary channel length of 536 m. The results showed that the water level in the primary canal for normal conditions is 0.1 m<Ynp<0.6 m. Additionally, the proposed system, which allows for real-time water supply monitoring, can increase rice production from two to three harvests per year.